1988
DOI: 10.3758/bf03209060
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a taste aversion conditioned with an odor-taste compound: Overshadowing is relatively weak in weanlings and decreases over a retention interval in adults

Abstract: Adult rats were injected with lithium chloride (LiCl) after consumption of a novel flavor (chocolate milk) that either was or was not presented together with a novel ambient odor (banana) as a compound conditioned stimulus (CS). In Experiment 1, the adults' consumption of the flavor 24 h after conditioning was compared with that of weanling rats given the same conditioning treatment on Postnatal Day 21. The results confirmed previous indications that the reduction in aversion observed for adults conditioned wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
38
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 16 publications
7
38
0
Order By: Relevance
“…The SOCR model (as the extended comparator hypothesis, which serves as its basis) has trouble to explain changes in responding to a CS as function of passage of time. Specifically, the SOCR model fails to explain relevant findings in the stimulus competition literature, such as spontaneous recovery of responding after overshadowing (Kraemer, Lariviere, & Spear, 1988) or blocking (Pineño, Urushihara, & Miller, 2005). The problem of the SOCR model is, not only that there is no mechanism by which passage of time could affect responding to a CS, but also that there is no obvious reason why the mechanisms already existing in the model should be affected by passage of time.…”
Section: Some Effects the Response Rule Can Explain (But Socr Cannot)mentioning
confidence: 73%
“…The SOCR model (as the extended comparator hypothesis, which serves as its basis) has trouble to explain changes in responding to a CS as function of passage of time. Specifically, the SOCR model fails to explain relevant findings in the stimulus competition literature, such as spontaneous recovery of responding after overshadowing (Kraemer, Lariviere, & Spear, 1988) or blocking (Pineño, Urushihara, & Miller, 2005). The problem of the SOCR model is, not only that there is no mechanism by which passage of time could affect responding to a CS, but also that there is no obvious reason why the mechanisms already existing in the model should be affected by passage of time.…”
Section: Some Effects the Response Rule Can Explain (But Socr Cannot)mentioning
confidence: 73%
“…This phenomenon, like the recovery achieved by reminder treatments, supports a performance-deficit view of cue competition while posing a problem to acquisition-deficit models because the blocked CS is assumed to not increase its associative strength without further training trials. Although spontaneous recovery of responding has been demonstrated after overshadowing (Kraemer, Lariviere, & Spear, 1988) and the relative stimulus validity effect (Cole, Gunther, & Miller, 1997), the study of spontaneous recovery following blocking has received little attention in the literature. Spontaneous recovery from the US-preexposure effect, which is often viewed as forward blocking by the context, was demonstrated by Batsell (1997) and J. S. Miller, Jagielo, and Spear (1993) using conditioned taste aversion preparations.…”
mentioning
confidence: 99%
“…Furthermore, recent work in the study of compound conditioning has focused on differences in aversion strength at various retention intervals (Batsell & Best, 1992a, 1992bKraemer, Lariviere, & Spear, 1988;Miller, Jagielo, & Spear, 1990). For example, Batsell and Best (l992b) demonstrated that both single-taste and overshadowed-taste aversions were significantly weaker at a short retention interval (i.e., 1 day) than at a longer one (i.e., 21 days).…”
mentioning
confidence: 99%